Analisis Pasang Surut Perairan Dumai Menggunakan Metode Admiralty - Kemala Fitri Astari; Andy Hendri; Manyuk Fauzi (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2018)
The admiralty method is a tidal harmonic analysis method that used to analyze and to predict tides. Tidal analysis with admiralty method is done using 15 days and 29 days tidal data. This research aims to analyze the initial time of tidal simulation which have the most accurate result. Tidal data of Port C of Pelindo, Dumai has been analyzed using 29 days admiralty method. The results of this research indicated that the results of tidal analysis using 29 days admiralty method generate the smallest RMSE (Root Mean Square Error) value of 28,67 cm which is the prediction result of initial time of 5 Hijri calender. So the most appropriate initial time of input data simulation for the purposes of tidal analysis is on the 5th of each month of the Hijri calendar or during the phase of the second month (crescent month. Keywords: admiralty method, tidal analysis, RMSE, Hijri calender